ANTIGENIC VARIATION AMONG PASTEURELLA MULTOCIDA ISOLATES FROM DISEASED BUFFALOES BY PROTEIN PROFILING AND CLUSTER ANALYSIS - M. Kamran; M. D. Ahmad; A. A. Anjum A. Maqbool; K. Muhammad; H. M. Khan; N. Hudda; M. Nawaz; M. A. Ali (Journal of Animal and Plant Sciences, 2014)
Hemorrhagic septicemia is an acute bacterial disease of buffaloes and cattle caused by Pasteurella multocida. In the present study, P. multocida (n=11) were isolated from healthy carrier (04/200) and diseased buffaloes (07/200) from Sargodha division, Punjab. Pasteurella multocida were identified by culture characteristics and biochemical profile index (API) Kit. Isolates were confirmed by serological and molecular characterization by PCR. Antigenic variation among P. multocida (11 isolates) and one vaccine strain was revealed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). Although SDS-PAGE revealed that five major proteins were present in all the isolates as well as in vaccine strain of P. multocida but isolates had variations in minor protein bands. Relatedness among the isolates was assessed by cluster analysis using fingerprint analysis of missing data (FAMD) and principal coordinate analysis (PCA) of 11 isolates and one vaccine strain. All isolates were clustered into 5 different groups namely I, II, III, IV and V on the basis of their electrophoretic profile. Group I, II, III, IV and V contained 1 (8.33%), 1(8.33%), 2 (16.67%), 6 (50%) and 2 (16.67%) isolates of P. multocida, respectively. Vaccine strain had high relatedness with group IV (S3, S6, S7, S8, and S9). It is concluded that distinct polypeptide variation is present among P. multocida isolates which insinuate for detailed proteomic and genomic analysis for the development of effective vaccines and control of hemorrhagic septicemia.
Keywords: Hemorrhagic septicemia; Pasteurella multocida; Buffaloes; PCR; Antigenic variation and protein profiling and cluster analysis